NCOG-25. EFFICACY OF ANTICONVULSANT THERAPY IN GLIOMA PATIENTS. (9th November 2020) - Medikonda, Ravi; Patel, Kisha; Saleh, Laura; Srivastava, Siddhartha; Jackson, Christina; Mohan, Aditya; Shah, Pavan; Weingart, Jon; Bettegowda, Chetan; Gallia, Gary; Brem, Henry; Lim, Michael
Abstract: Gliomas account for 30% of primary brain tumors and can frequently present with seizures. There are few guidelines for usage of anticonvulsant therapy in glioma patients. Some clinicians utilize anticonvulsant therapy in all glioma patients as a means of prophylaxis, whereas other clinicians prescribe anticonvulsant therapy only in patients that experience seizures. In this single-institution retrospective cohort study, we evaluate the effect of commonly prescribed anticonvulsant levetiracetam on incidence of post-operative seizures and overall survival in primary glioma patients. 436 patients met the inclusion criteria for this study. 35% of patients presented with a pre-operative seizure and 63% of patients received pre-operative Levetiracetam. The incidence of a seizure within 1 year of tumor resection was 31%. On multivariate logistic regression analysis of patient pre-operative clinical and imaging characteristics, it was found that only a pre-operative seizure (p = 0.02) significantly increased the odds of a post-operative seizure within 1 year of tumor resection. Neither pre-operative levetiracetam (p = 0.31), intra-operative levetiracetam (p = 0.59), or post-operative levetiracetam (p = 0.75) significantly reduced the odds of a post-operative seizure. Using a cox proportional hazards model, pre-operative levetiracetam (p = 0.11), intra-operative levetiracetam (p = 0.34), and post-operative levetiracetam (p = 0.88) do not significantly affect overall survival. Our findings reveal that glioma patients are often prescribed anticonvulsant medication regardless of whether they have had a pre-operative seizure. Most patients also receive anti-convulsant medication in the peri-operative and post-operative setting regardless of whether they have had pre-operative or immediate post-operative seizures. Use of pre-operative or intra-operative levetiracetam as a prophylactic measure does not impact the incidence of post-operative seizures. Furthermore, anti-convulsant therapies do not demonstrate a survival benefit in our study. These results provide a rationale for re-evaluating the use of anti-convulsant medications in glioma patients that do not have seizure symptoms.